2013
DOI: 10.1186/1471-2458-13-392
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and related factors of nonfatal injuries among adolescents and college students in Shenzhen city of China

Abstract: BackgroundInjuries impact adolescents and young adults in unique ways. The purpose of this study was to determine the incidence rate of nonfatal injuries, and identify characteristics and risk factors for the injuries among adolescents and college students in Shenzhen, China.MethodsA total of 4,138 students from 79 classes were selected using a purposive sampling method in 2010. The questionnaire included personal demographics, behavioral factors, and self-perceived agrypnia. Stepwise multivariate logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 24 publications
5
22
0
Order By: Relevance
“…As expected, the rate of fall was significantly higher in males than females. This study conforms to other reports that have identified falls as the predominant cause of injury among adolescents [12,28,33,35,36]. The prevention of falls is undetermined by the numerous factors leading up to them, thus this is a challenge for both school and community based education program.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As expected, the rate of fall was significantly higher in males than females. This study conforms to other reports that have identified falls as the predominant cause of injury among adolescents [12,28,33,35,36]. The prevention of falls is undetermined by the numerous factors leading up to them, thus this is a challenge for both school and community based education program.…”
Section: Discussionsupporting
confidence: 90%
“…Considerable numbers of studies around the globe has reported similar findings [7,8,10,12,28]. This is probably because males have higher levels of sensation seeking [29][30][31], and are more impulsive [32] thus are more likely to engage in risky behaviour than females [32][33][34].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In his paper on injuries and social determinants among in-school adolescents in six African countries, Peltzer [13] also don't find a link with physical activity but he found association with smoking and drinking. It is the same observations in a Chinese cohort of students, for Zhou, Chen and Dong [44] which found an association with alcohol consumption but also with the trying smoking behavior. Muula [7] and colleagues, in their study based on the data of the Djibouti Global School-based Health Survey, found that adolescents who smoke cigarettes were more likely to report injuries.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the injuries types, this indicator was much more associated in case of work injuries and to a lesser extent in case of traffic injuries but these observations remained not in multivariate models. However, Zhou, Chen and Dong [44] have found an increase of the injury proportions with the increase of the self-perceived agrypnia in a cohort of Chinese students. Also, Li [58] and colleagues have shown a negative association between sleep duration and occurrence of injuries among school-aged children in rural China.…”
Section: Discussionmentioning
confidence: 90%